Parent–Child Relationships, Parental Control, and Adolescent Mental Health: An Empirical Study Based on CEPS 2013–2014 Survey Data - Tao Xu; Jiyan Ren (Behavioral Sciences)
Previous research has consistently showed a close relationship between the quality of parent–child relationships and adolescents’ mental health. However, the relationship between parental control and adolescents’ mental health has remained controversial. This study utilized baseline data from the China Education Panel Survey (CEPS 2013–2014) to analyze the impact of parent–child relationships on adolescents’ mental health. The results indicated that parent–child relationships significantly influenced adolescents’ mental health. Parental control moderated the impact of parent–child relationships on adolescents’ mental health: When the parent–child relationship was good, appropriate behavioral control by parents strengthened the positive effect of a good parent–child relationship on adolescent mental health. Conversely, when the parent–child relationship was poor, parental control intensified the negative impact of a poor parent–child relationship on adolescent mental health. Furthermore, heterogeneity analysis revealed gender differences in the moderating effect of the parent–child relationship: compared to boys, the moderating effect of parental control on the parent–child relationship was more significant among girls.